2019
DOI: 10.1053/j.jvca.2018.11.002
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Point-of-Care Ultrasound Monitoring in Cardiac Surgical Patients With Acute Kidney Injury

Abstract: The approach to the patient with acute kidney injury (AKI) after cardiac surgery involves multiple aspects. These include the rapid recognition of reversible causes, the accurate identification of patients who will progress to severe stages of AKI, and the subsequent management of complications resulting from severe renal dysfunction. Unfortunately, the inherent limitations of physical examination and laboratory parameter results are often responsible for suboptimal clinical management. In this review article,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 128 publications
1
42
0
Order By: Relevance
“…12). The pattern of the interlobar vein Doppler signal is affected by central venous compliance [51,52]. A normal venous pattern is continuous (Fig.…”
Section: Whobus In the Oligo-anuric Patientmentioning
confidence: 99%
See 2 more Smart Citations
“…12). The pattern of the interlobar vein Doppler signal is affected by central venous compliance [51,52]. A normal venous pattern is continuous (Fig.…”
Section: Whobus In the Oligo-anuric Patientmentioning
confidence: 99%
“…Those patients (Fig. 12E) will experience a rapid decrease in glomerular filtration rate [18,19,52] and a higher risk of death [51] (Fig. 12).…”
Section: Whobus In the Oligo-anuric Patientmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no studies have explored the effect of ultrafiltration feedback control on patient outcomes. 155,161,162 In addition, these "intelligent" systems should be used with caution, and some researchers advocate cross-checking with other technologies (e.g., bioimpedance) to prevent exposing the patient to chronic fluid overload. 163 Other studies have suggested that sodium and ultrafiltration profiling may partly preserve intradialytic hemodynamic status, but sodium profiling may aggravate intradialytic salt loading, resulting in thirst and high interdialytic weight gain with chronic fluid overload.…”
Section: Intradialytic Hemodynamic Stabilitymentioning
confidence: 99%
“…Echocardiographic examinations may be possible at the point-of-care by the clinicians already taking care of these children with suspected or proven coronavirus infection. [18][19] This approach is advantageous not only for patient convenience but also for infection control. The final location for an echocardiographic examination will often require thoughtful consideration of the following factors: risk of viral transmission, including pregnant women; monitoring capabilities; and, staffing requirements.…”
Section: Consider the Venue Selection For Imagingmentioning
confidence: 99%